CONTINUOUS PROCESS OF OLEFINIC EPOXIDATION BY SUPPORTED HETEROPOLY ACID (2015)
The subject invention is related to a continuous process of epoxidation of an olefin with supported heteropoly acid catalyst, which does not involve the use of an additive(s). The subject invention separates the products and oxides through a continuous process to reduce backmixing, thereby achieving an efficacy equal to that of a process involving the use of an additive. By excluding additives from the process, the subject invention has a lower cost, and avoids the need for additional wastewater treatment since no alkali metal or alkali earth metal compound is formed during the reaction. Moreover, the continuous process of the invention is also beneficial in industrial manufacturing.